Identification of Small‐Molecule Modulators of Diguanylate Cyclase by FRET‐Based High‐Throughput Screening. (27th December 2018) - Christen, Matthias; Kamischke, Cassandra; Kulasekara, Hemantha D.; Olivas, Kathleen C.; Kulasekara, Bridget R.; Christen, Beat; Kline, Toni; Miller, Samuel I.
Abstract: The bacterial second messenger cyclic diguanosine monophosphate (c‐di‐GMP) is a key regulator of cellular motility, the cell cycle, and biofilm formation with its resultant antibiotic tolerance, which can make chronic infections difficult to treat. Therefore, diguanylate cyclases, which regulate the spatiotemporal production of c‐di‐GMP, might be attractive drug targets for control of biofilm formation that is part of chronic infections. We present a FRET‐based biochemical high‐throughput screening approach coupled with detailed structure–activity studies to identify synthetic small‐molecule modulators of the diguanylate cyclase DgcA from Caulobacter crescentus . We identified a set of seven small molecules that regulate DgcA enzymatic activity in the low‐micromolar range. Subsequent structure–activity studies on selected scaffolds revealed a remarkable diversity of modulatory behavior, including slight chemical substitutions that reverse the effects from allosteric enzyme inhibition to activation. The compounds identified represent new chemotypes and are potentially developable into chemical genetic tools for the dissection of c‐di‐GMP signaling networks and alteration of c‐di‐GMP‐associated phenotypes. In sum, our studies underline the importance of detailed mechanism‐of‐action studies for inhibitors of c‐di‐GMP signaling and demonstrate the complex interplay between synthetic small molecules and the regulatory mechanisms that control the activity of diguanylate cyclases. Abstract : Controling biofilm formation : Diguanylate cyclases (DGCs) are attractive anti‐invective drug targets for control of biofilm formation. We report a FRET‐based HTS assay coupled with detailed structure–activity studies to identify modulators of DGCs. Detailed mechanism‐of‐action studies demonstrate the complex interplay between the synthetic compounds and the regulatory mechanisms that control the activity of DGCs.